Efeito Cézanne: uma abordagem epistemológica à experiência da percepção e do pensamento entre arte e ciência - Vasconcellos Filho, Miguel de Frias e (2008)
This paper rises an epistemological discussion, based in point of view of thinkers about perception, thoughts and intuition, mainly starting in Gaston Bachelard s analysis, envolving Art and Science. This paper, without intention to get answers, tried to make an artist-work-thinkers relation, started in search of comprehension of doubts and unrests, during the elaboration of Paul Cézanne s work (1839-1906), a name well-known, respected and considered in art universe, mainly found in letters wrote to his friend and confident Émile Bernard, to his son Paul; based in close person s narratives like Vollard s, and from impressions and percepcions of Rainer Maria Rilk, poet an art observer, which after know the Cézanne art, began a detailedly analysis. As oposition, was used the point of view of scientists accustomed with straightness of racional thought